Christian Conversion and Colonial "Native Policy": The Role of Missionaries in Formulating Reservation Policy in German Southwest Africa. Issue 4 (December 2020) - Morgan, Stephen
Abstract: This article examines how German Protestant missionaries to the Herero people influenced colonial "native policy" in German Southwest Africa in the years leading up to the Colonial War of 1904 to 1907. By the late 1890s, burgeoning European settlement increasingly displaced the Herero from their traditional territory. While colonial officials promoted more settlement, missionaries had developed a concept of conversion that linked Christianization with living in self-sufficient agricultural communities, and hoped to place limits on Herero displacement. Thus, missionaries and colonial officials engaged in protracted political negotiations over the creation of inalienable "native reservations" for the Herero. I show that missionaries' model of Herero conversion prompted them to promote an alternative mode of settler colonialism that would make room in Southwest Africa for self-sufficient Herero settlements. Prior to the Colonial War, missionaries succeeded in convincing the colonial government to begin creating reservations, thus shaping colonial policy according to missionary priorities.